Neuromancer eaudiobook - Gibson, William (Sprawl Trilogy, 2011)
Twenty years ago, it was as if someone turned a light on. The future blazed into existence with each deliberate word that William Gibson laid down. Neuromancer didn’t just explode onto the science fiction scene. It permeated into our consciousness, our culture, our science, and our technology. The winner of the Hugo, Nebula, and Philip K. Dick Awards, Neuromancer showed us what we were capable of creating and what we were capable of destroying—and illuminated the dark corners of the path we were headed down. Today, we have this science fiction masterpiece to thank for the term “cyberpunk,” for easing our way into the information age and Internet society.   Neuromancer’s virtual reality has become our own. And yet, William Gibson’s gritty, sophisticated vision still manages to inspire the minds that will take us ever further into the future.